Ireland's economic crisis and austerity: the response of the Irish Catholic Bishops - Moran, Joe (Journal of contemporary religion, 2019)
The Irish Roman Catholic Church has been a dominant institution in Irish society for generations but this dominance has declined in recent decades due to modernisation and secularisation. Since the mid-1990s, the Church has been rocked by scandals of clerical and religious sex abuse of children, which has had a negative impact on its moral standing in Irish society. As a result of the economic crash in 2008, a programme of severe austerity was introduced by the Irish government. In this article, the response of the Irish Catholic Bishops to the recession and austerity measures is assessed through the analysis of their public statements which are available through the news archive of the Irish Bishops' Conference. The findings show that the Bishops did criticise the socio-economic policies of the Irish government but this was limited due to a range of institutional barriers.